1984
DOI: 10.1063/1.864482
|View full text |Cite
|
Sign up to set email alerts
|

Determination of laser intensity and hot-electron temperature from fastest ion velocity measurement on laser-produced plasma

Abstract: Saturation gain-length product during short-wavelength plasma lasing Appl. Phys. Lett. 101, 081105 (2012) Laser induced avalanche ionization in gases or gas mixtures with resonantly enhanced multiphoton ionization or femtosecond laser pulse pre-ionization Phys. Plasmas 19, 083508 (2012) A new scheme for stigmatic x-ray imaging with large magnification Rev. Sci. Instrum. 83, 10E527 (2012) Additional information on Phys. Fluids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The scaling laws of the maximum proton energy with laser power density delivered by ps-and fs-laser (Tan et al, 1984;Clark et al, 2000;Krushelnick et al, 2007) predict a maximum energy of the protons produced with the subnanosecond 3-TW laser system PALS to be about 1 MeV. Nevertheless, the use of an ion collector shielded with 8-μm Al foil, in order to absorb the extreme ultraviolet pulse inducing the "photopeak" in the IC signal , brought clear-cut evidence that the fastest protons have energy up to about 4 MeV .…”
Section: Introductionmentioning
confidence: 99%
“…The scaling laws of the maximum proton energy with laser power density delivered by ps-and fs-laser (Tan et al, 1984;Clark et al, 2000;Krushelnick et al, 2007) predict a maximum energy of the protons produced with the subnanosecond 3-TW laser system PALS to be about 1 MeV. Nevertheless, the use of an ion collector shielded with 8-μm Al foil, in order to absorb the extreme ultraviolet pulse inducing the "photopeak" in the IC signal , brought clear-cut evidence that the fastest protons have energy up to about 4 MeV .…”
Section: Introductionmentioning
confidence: 99%
“…This is stronger than the ðIk 2 Þ 1=3 scaling associated with resonance absorption (RA) that is widely observed in other experiments. 4,5 In addition, it has been shown that these protons carry less than 0.3% of the laser energy. 1 Finally, the late-time behavior of the target voltage has been inferred 6 and associated return currents have been studied.…”
mentioning
confidence: 99%
“…4,5 Much effort has been devoted to the study of the empirical conditions which drive these instabilities and how maximum ion energy scales with laser intensity. [6][7][8] On-target laser intensities approaching 10 15 W/cm 2 in OMEGA ICF implosions result in fast ablator ion energy endpoints of order ∼1 MeV. 9 Certain HED plasma experiments at OMEGA and the National Ignition Facility (NIF) have configurations with unique geometries and unusually high laser intensity which result in large fast ablator ion energies.…”
Section: Introductionmentioning
confidence: 99%